2017
DOI: 10.1080/07347332.2017.1379582
|View full text |Cite
|
Sign up to set email alerts
|

The effects of individual- and network-level factors on discussion of cancer experiences: Survivors of childhood cancer in Korea

Abstract: This study aimed to identify young adult Korean cancer survivors' individual- (psychological distress, stigma, sociodemographic variables, and cancer-related variables) and network-level factors (relationship type, social support type) that influence discussion of their cancer experiences. Sixty-eight survivors of childhood cancer who were recruited using snowball sampling nominated 245 individuals from their networks, including family and intimate partners (40%) and friends and acquaintances (60%), as people … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 39 publications
0
2
0
1
Order By: Relevance
“…In this sense, a korean study pointed out the strength of social network of cancer patients, through developing of group meetings, favoured coping with the illness and imporved their quality of life because individuals generate support through sharing their experiences, difficulties and strategies used to coping with them. 22 Organizing educational activities with groups of patients and family members was also suggested by a spanish study, in order to identify early different issues and concerns that can emeerge througout the treatment. It's an effective initiative to give specific guidance, enabling sharing experiences and concerns among equals, as they receive suggestions that can assist them to face the process.…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, a korean study pointed out the strength of social network of cancer patients, through developing of group meetings, favoured coping with the illness and imporved their quality of life because individuals generate support through sharing their experiences, difficulties and strategies used to coping with them. 22 Organizing educational activities with groups of patients and family members was also suggested by a spanish study, in order to identify early different issues and concerns that can emeerge througout the treatment. It's an effective initiative to give specific guidance, enabling sharing experiences and concerns among equals, as they receive suggestions that can assist them to face the process.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to strengthening the evidence for certain themes identified in previous studies, this study revealed that parents felt cancer stigma after the diagnosis of childhood leukaemia. This psychological reaction exists not only in families living with childhood leukaemia survivors but also in the early process after diagnosis (Kim et al, 2018; Yi et al, 2016). Combined with the results of previous studies (Grau et al, 2010), the word leukaemia has a strong social stigma.…”
Section: Discussionmentioning
confidence: 99%
“…Os trechos a seguir apresentam os fluxos de encaminhamentos ao serviço de referência para tratamento oncológico relatados ou referidos pelos participantes da pesquisa: A equipe de saúde, em especial a da atenção primária, deve protagonizar a relação de confiança com os pacientes, pois este vínculo favorece a comunicação terapêutica, a qual, por sua vez, facilita o enfrentamento do adoecimento e ameniza a sobrecarga psicológica que o indivíduo vivencia juntamente com seus familiares (BARROS et al, 2019). Há evidências de que uma comunicação inadequada ou insuficiente, caracterizada por informações incompletas, que fazem alusão ao medo e não esclarecem as condições de evolução da doença e tratamento, pode prejudicar a tomada de decisão diante das necessidades de cuidado (SOARES; SANTOS; ARRUDA, 2017;KIM et al, 2018;TESTON et al, 2018;JANAH et al, 2020).…”
Section: O Início Da Históriaunclassified